PERAN MAHASISWA KKN DALAM MENINGKATKAN MINAT BELAJAR SISWA MELALUI MEDIA PEMBELAJARAN DI SD GMIM RAANAN BARU - Supit, Sugijanti; Palar, Yolanda; Pangemanan, Juwita; Hinonaung, Gratia; Mangalo, Yuliana; Makalisang, Yudian; Tinengke, Yudince I; Bulasing, Maruanto; Rading, Elsa; Makawalengke, Yeremia (HOSPITALITAS: Jurnal Pengabdian Kepada Masyarakat, 2024)
The problem that still often occurs in the world of education, especially at the elementary school level, is the lack of interest in learning from students. This is caused by the limitations of learning media. With these constraints, the researcher aims to play a role in increasing students' interest in learning at GMIM Raanan Baru Elementary School through learning media. This study uses qualitative research methods, using observation techniques. This observation technique is carried out by direct observation of the situation in the field. The location of this research was SD GMIM Raanan Baru, West Motoling district. This research is a form of KKN student service during the KKN period from 6 February – 8 March 2023. With the role of students through the service carried out, students at GMIM Raanan Baru Elementary School have an increased interest in learning.